The Evolutionary Pattern of Glycosylation Sites in Influenza Virus (H5N1) Hemagglutinin and Neuraminidase - Chen, Wentian; Zhong, Yaogang; Qin, Yannan; Sun, Shisheng; Li, Zheng (PLOS ONE, 2012)
Two glycoproteins, hemagglutinin (HA) and neuraminidase (NA), on the surface of influenza viruses play crucial roles in transfaunation, membrane fusion and the release of progeny virions. To explore the distribution of N-glycosylation sites (glycosites) in these two glycoproteins, we collected and aligned the amino acid sequences of all the HA and NA subtypes. Two glycosites were located at HA0 cleavage sites and fusion peptides and were strikingly conserved in all HA subtypes, while the remaining glycosites were unique to their subtypes. Two to four conserved glycosites were found in the stalk domain of NA, but these are affected by the deletion of specific stalk domain sequences. Another highly conserved glycosite appeared at the top center of tetrameric global domain, while the others glycosites were distributed around the global domain. Here we present a detailed investigation of the distribution and the evolutionary pattern of the glycosites in the envelope glycoproteins of IVs, and further focus on the H5N1 virus and conclude that the glycosites in H5N1 have become more complicated in HA and less influential in NA in the last five years.